Analisis Butir Soal Penilaian Akhir Semester Gasal Kelas XI dan XII Jurusan Teknik Komputer dan Jaringan SMK Muhammadiyah 1 Salam - Mustofa Yulian Said; Eko Mapanaji (Journal of Information Technology and Education (JITED), 2025)
The purpose of this study was to determine the results of the analysis of multiple choice questions on the End of Gasal Semester Assessment in the subject of Network Service Technology class XI and XII majoring in Computer and Network Engineering at SMK Muhammadiyah 1 Salam in the 2022/2023 school year. This research uses documentation type data collection techniques. The data taken to support the research process are student exam question sheets, answer keys to question sheets, student answer sheets, syllabus, exam grids. Before entering the item analysis test stage, the data will first be tested for validity by expert lecturers. Expert lecturers assess evaluation instruments based on material, construction and language aspects. After completion, the next is the process of analyzing the items with the aim of obtaining the value of the aspects of item validity, reliability, effectiveness of triggers, differentiating power and the level of difficulty of a test. This research is a type of quantitative descriptive research where the subjects are 30 students of class XI TKJ and 37 students of class XII TKJ. The results of this study are addressed by 4 items (16%) with good quality, 5 items (20%) of sufficient quality, 8 items (32%) categorized as not good, and 8 items (32%) categorized as very bad for class XI TKJ questions. Meanwhile, class XII TKJ questions have the results of 4 items (16%) of good quality, 7 items (28%) of sufficient quality, 8 items (32%) categorized as not good and 6 items (24%) categorized as very bad.